The weight of phonological vs. phonetic accent in teaching pronunciation : Implications and applications - Odisho, Edward Y. (Linguarum Arena, 2017)
Teaching pronunciation especially in Second Language (L2) and Foreign Language (FL) learning situations has traditionally involved some haphazard practices and procedures such as dealing with it mechanically and exclusively through modeling by the instructor and repetition by the learner as if speech is a mechanical skill and the exclusive function of the auditory sense. Moreover, teaching pronunciation in those situations has often failed to focus on aspects that are more important for eff ective and effi cient communication and comprehension. Generally speaking, this paper is an attempt at shifting the pedagogy of teaching pronunciation in the cognitive direction since speech is physical only at its surface structure, but distinctly cognitive at its deep structure with the brain being at the helm of the effi cient process of speech. This pedagogical shift is premised on two major principles. First, it promotes a multisensory (auditory, visual, tactile-kinesthetic) and multicognitive (think, associate, analyze, synthesize etc…) approach (MMA) to replace the exclusively auditory one and build sets of teaching and learning strategies based on those three senses to function jointly whenever relevant. Second, to respond to the failure to secure effi cient pronunciation with no or with minimum accent, the dichotomy of phonological accent vs. phonetic accent is introduced. Phonological accent results from mispronunciations that lead to radical semantic (meaning) change, whereas phonetic accent rarely interferes with meaning. From a didactic perspective, priority in teaching L2 or FL pronunciation should be geared in the direction of overcoming phonological accent fi rst and then work on phonetic accent.